Object-oriented and classical software engineering - Schach, Stephen R. (McGraw-Hill Higher Education, 2005)
The book is designed for an introductory software engineering course. It provides an excellent introduction to software engineering fundamentals, covering both traditional and object-oriented techniques. The book has been updated to use the Unified Process model throughout, making the text more practical and modern. The material has also been revised to conform to the latest ISO/IEC 12207 standards. Additionally, the references and examples have been thoroughly updated to appeal to today's student